2023
DOI: 10.3390/coatings14010006
|View full text |Cite
|
Sign up to set email alerts
|

TiAl-Based Oxidation-Resistant Hard Coatings with Different Al Contents Obtained by Vacuum-Pulse-Arc Granule Melting

Alexander N. Sheveyko,
Konstantin A. Kuptsov,
Philipp V. Kiryukhantsev-Korneev
et al.

Abstract: A method was proposed for increasing the oxidation resistance of promising wrought Ti2AlNb ortho-alloys by depositing γ-TiAl-based coatings. Using original vacuum pulse-arc melting of 100 μm thick granule layers, coatings with different Al/Ti ratios and a thickness of 50–60 µm were obtained on the surface of the Ti50Al25Nb25 alloy. Granules Ti50Al44Nb4.9Mo1B0.1 (at.%), 20–60 μm in size, were employed. To vary Al content, initial granules and their mixture with Al powder were used. Excellent adhesion of the coa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…The applied materials and the application field of the other technologies for Ti-Albased alloys are presented in Table 7. The other fabrication technologies by Ti-Al-based alloys are selected and located in the surface enhancement technologies field, including coating [87], welding, grinding and polishing, joining, hard facing, repair, creating parts of Ti-Al-based alloys as raw materials using layer-by-layer deposition, hydrogenationdehydrogenation, and coating of Ti-Al-based alloys [88] on the substrate by applying powder on the substrate and/or the prepared semifinished products, which all are widely used in some technical fabrications and application fields. In the section on the "basic research on Ti-Al based alloys", the analysis of the basic research on Ti-Al-based alloys showed that Ti-Al-based alloys mostly contained approximately 43-50 at% aluminum.…”
Section: Analysis Of 25 Other Fabrication Technologies By Ti-al-based...mentioning
confidence: 99%
“…The applied materials and the application field of the other technologies for Ti-Albased alloys are presented in Table 7. The other fabrication technologies by Ti-Al-based alloys are selected and located in the surface enhancement technologies field, including coating [87], welding, grinding and polishing, joining, hard facing, repair, creating parts of Ti-Al-based alloys as raw materials using layer-by-layer deposition, hydrogenationdehydrogenation, and coating of Ti-Al-based alloys [88] on the substrate by applying powder on the substrate and/or the prepared semifinished products, which all are widely used in some technical fabrications and application fields. In the section on the "basic research on Ti-Al based alloys", the analysis of the basic research on Ti-Al-based alloys showed that Ti-Al-based alloys mostly contained approximately 43-50 at% aluminum.…”
Section: Analysis Of 25 Other Fabrication Technologies By Ti-al-based...mentioning
confidence: 99%